Perlindungan Hukum Hak Cipta Buku di Pasar Digital dan Tanggung Jawab Marketplace - Cita Tsaabiethah Agustria Sasti; Zaenal Arifin; Agus Saiful Abib; Muhammad Sibaweh Muamar (JURNAL USM LAW REVIEW, 2026)
This study aims to analyze the forms of legal protection for copyright holders of books that are illegally reproduced in digital markets, as well as the legal consequences for perpetrators under Law Number 28 of 2014 concerning Copyright. The widespread practice of book piracy through digital marketplaces indicates that the development of information technology not only expands the distribution of creative works but also increases the risk of copyright infringement on a massive scale. This research employs a normative juridical method with a statutory approach and qualitative analysis of secondary data through library research. The findings show that legal protection is implemented through both preventive and repressive measures, including the strengthening of copyright holders’ exclusive rights, the active obligations of digital marketplaces, mechanisms for recording works, and the enforcement of civil, criminal, and administrative sanctions. The effectiveness of such protection depends on consistent law enforcement, public legal awareness, and the active responsibility of digital platforms in preventing the circulation of pirated books. The novelty of this study lies in its integrated analysis positioning digital markets as both active legal subjects and transaction intermediaries within the framework of copyright protection in the digital economy era. Penelitian ini bertujuan menganalisis bentuk perlindungan hukum bagi pemegang hak cipta buku yang digandakan secara ilegal di pasar digital serta akibat hukum bagi pelaku berdasarkan Undang-Undang Nomor 28 Tahun 2014 tentang Hak Cipta. Maraknya pembajakan buku melalui marketplace menunjukkan bahwa perkembangan teknologi informasi memperluas distribusi karya sekaligus meningkatkan risiko pelanggaran hak cipta secara masif. Penelitian ini menggunakan metode yuridis normatif dengan pendekatan peraturan perundang-undangan dan analisis kualitatif terhadap data sekunder melalui studi kepustakaan. Hasil penelitian menunjukkan bahwa perlindungan hukum dilakukan melalui upaya preventif dan represif, meliputi penguatan hak eksklusif pemegang hak cipta, kewajiban aktif marketplace, mekanisme pencatatan ciptaan, serta penerapan sanksi perdata, pidana, dan administratif. Efektivitas perlindungan tersebut bergantung pada konsistensi penegakan hukum, kesadaran hukum masyarakat, dan tanggung jawab platform digital dalam mencegah peredaran buku bajakan. Kebaruan penelitian ini terletak pada analisis terpadu yang menempatkan pasar digital sebagai subjek hukum aktif sekaligus perantara transaksi dalam kerangka perlindungan hak cipta di era ekonomi digital.
Keywords: Buku; Hak Cipta; Pasar Digital; Perlindungan Hukum